Participatory and Conventional Investigation of Tick Infestation in Camels and Cattle of Somali Pastoral Areas, Eastern Ethiopia - Mohamoud Mohamed Jama; Hassan Abdi Hussein; Shaban Mohamed Abdi; Teka Feyera (Journal of Parasitology Research)
Ticks are a common parasite that affect many animals by causing slowed growth, reduced milk output, and financial losses for industries that depend on animal hides and skins. From June to December 2017, participatory and conventional investigations on tick infestation in camels and cattle were conducted in Kebribayah and Afdem districts of Ethiopia’s Somali Regional State. The aim of this study was to determine the prevalence and density of ticks in these animals and establish strategic control measures to enhance livestock productivity and livelihoods in pastoral areas. The current study found that the prevalence of tick infestation in Kebribayah and Afdem districts was 83.3% and 86.8%, respectively. Rhipicephalus pulchellus (48.9%) was identified as the most common tick species in camels and cattle, followed by Amblyomma gemma (26.3%), Hyalomma truncatum (11.6%), Amblyomma lepidum (6.7%), and Amblyomma variegatum (6.5%). Among the variables considered, age and body condition score were significant risk factors (p<0.001). Tick density varied depending on the recorded months and seasons (p<0.001), with the highest mean tick density occurring in November (32.69±21.750) and during the wet season (28.56±19.750). Livestock owners in Kebribayah and Afdem ranked topical acaricide application as the most effective tick control method, followed by ivermectin injections, with the traditional hand removal method being the least effective. These rankings were consistent across both districts, and there was moderate agreement among livestock keepers from both regions regarding the best method. Afdem livestock keepers had slightly weak agreement on high tick burden in spring (W=0.475, p=0.127), and Kebribayah livestock keepers showed slightly strong agreement in tick burden across seasons (W=0.700, p=0.038), with spring having a significantly higher burden than winter. Consequently, participatory appraisal indicated that ticks were important and prevalent ectoparasites in the study area. Finally, strategic tick control appropriate for specific management and production environments should be implemented biannually in wet seasons.